The Virtue of the Green: Plant Agency and Interspecies Communion in Mary Oliver’s Devotions (2017) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This article conducts a close reading of Mary Oliver’s poetry collection, Devotions (2017), to elucidate a novel ecological ethic regarding trees and an interspecies love that transcends the confines of human-centric and anthropomorphic frameworks. While anthropocentric perspectives assert human supremacy through the exclusive possession of soul and intellect, Oliver destabilizes these assumptions. She hypothesizes the existence of plant souls and replaces traditional cognition with a value system rooted in ‘plant virtue,’ a concept that compels humans to question their own ontological hierarchy. This virtue of plants serves as a central thesis in her work, leading to a critical interrogation of dominant human practices, such as the consumption of vegetation. Finally, the article explores the vivid interspecies affection in Oliver’s oeuvre, specifically through the lens of queering the non-human. Her poetic engagement with flora opens new possibilities for human sexuality and intimacy with the botanical world. To substantiate these claims, this study employs the theoretical framework of plant humanities, conceptualized as a novel ecocritical approach aimed at dismantling the anthropocentric hierarchies often imposed upon the botanical realm. Furthermore, it utilizes the lens of “queering the non-human”—as articulated by scholars such as Giffney & Hird and Luciano & Chen—to elucidate how Oliver’s poetry envisions deeply “queer,” affective, and more hopeful modes of empathetic kinship with plant life.